Experiential Learning Kewirausahaan: Mengasah Ide Bisnis Pelajar dengan Lembar Kerja dan Business Model Canvas - Siti Mahmudah; Habiburrochman; Eko Tjiptojuwono; Fri Medistya Anke Priyono (Jurnal Ragam Pengabdian, 2026)
This community engagement program aimed to strengthen secondary students’ entrepreneurial competence through an experiential-learning-based training that integrates an idea-analysis worksheet (positive–negative) as scaffolding and Business Model Canvas (BMC) development. The program was conducted at SMA Mujahidin Surabaya on 27 January 2023 in a single intensive session (approximately 2 hours) involving 99 students. The implementation followed Kolb’s experiential learning cycle (concrete experience, reflective observation, abstract conceptualization, and active experimentation) delivered in four stages: character and idea elicitation, worksheet completion, BMC drafting, and presentation/reflection. Evaluation was carried out through participatory observation and artifact assessment using predefined indicators for the worksheet and each BMC block; achievement was calculated as the percentage of participants meeting the indicators. Results indicate that 85% of students completed the worksheet accurately and 78.5% completed all nine BMC blocks. The main difficulties were found in the financial blocks (cost structure and revenue streams), suggesting the need for staged financial-literacy support in follow-up sessions. Overall, the approach shows promise as a practical and replicable model for entrepreneurship education at the secondary level.